Mechanism and Protective Effect of Smilax glabra Roxb on the Treatment of Heart Failure via Network Pharmacology Analysis and Vitro Verification - Long, Yingxin; Li, Zunjiang; Huang, Chunxia; Lu, Zhongyu; Qiu, Kuncheng; He, Meixing; Fang, Zhijian; Ding, Banghan; Yuan, Xiaohong; Zhu, Wei (Frontiers in Pharmacology, 2022)
Smilax glabra Roxb (SGR) has been widely applied alone or combined with other Chinese herbs in heart failure (HF), but its mechanism and protective effect have not been investigated. We aimed to explore the mechanism and protective effect of SGR on the treatment of HF. Network pharmacology analysis predicted that SGR was involved in regulation of the cell proliferation, oxidation-reduction process, apoptotic process, ERK1 and ERK2 cascade, and MAPK cascade etc, its mechanism was mainly involved in MAPK signaling pathway, Calcium signaling pathway, Cardiac muscle contraction etc. Subsequently, SGR was proved to improve cellular viability, restore cellular morphology, suppress cellular and mitochondrial ROS production, improve H2O2-induced lysosome inhibition, attenuate mitochondrial dysfunction, protect mitochondrial respiratory and energy metabolism in H9c2 cells. It activated p38MAPK pathway by decreasing the mRNA expression of AKT, PP2A, NF-KB, PP2A, RAC1, CDC42 and the protein expression of ERK1, ERK2, JNK, Bax, Caspase3, increasing the mRNA expression of Jun, IKK, Sirt1 and the protein expression of p38MAPK and Bcl-2. In addition, Istidina and trans-resveratrol with highest degree was identified in SGR via UHPLC-LTQ-Orbitrap-MSn method, and were suggested as anti-heart failure agents by targeting SRC, JUN respectively with molecular docking analysis. In conclusion, SGR may have protective effect on HF through cellular and mitochondrial protection via multi-compounds and multi-targets, its mechanism may be involved in activating p38 MAPK pathway, Istidina and trans-resveratrol acid may be possible anti-HF agents by targeting SRC, JUN respectively.